Protective effect of erythropoietin against myocardial injury in rats with sepsis and its underlying mechanisms - ZHANG, XINLIANG (Mol Med Rep, 2015)
The aim of this study was to investigate the protective effect of erythropoietin (EPO) against acute myocardial injury and its underlying mechanisms. Mice (n=146) were randomly divided in a double-blind manner into four groups, sham, Rocephin, EPO and sepsis, and mortality was observed on the seventh day after cecal ligation and puncture. In addition, a total of 252 rats were randomly divided into three groups, sham, EPO and sepsis, and indicators of cardiac function, inflammatory mediators and serum creatine kinase levels were assessed. Mitochondrial membrane potential, cell apoptosis and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) p65 expression levels were detected using flow cytometry. Following intervention with EPO, the mortality rate in mice with sepsis was significantly reduced and the cardiac function of septic rats was significantly improved. In addition, the levels of inflammatory mediators, serum creatine kinase and apoptosis and the myocardial mitochondrial membrane potential and expression of NF-κB p65 in cardiac tissue were all improved following EPO treatment, and the differences between the results for the sepsis and EPO groups were statistically significant (P<0.05). These findings suggest that EPO reduces the myocardial inflammatory response in septic rats, attenuates the reduction in mitochondrial membrane potential and inhibits myocardial cell apoptosis by reducing NF-κB p65 expression, and therefore exerts a protective effect in the myocardium.